Security in Open Model Software with Hardware Virtualisation – The Railway Control System Perspective - Feuser, Johannes; Peleska, Jan (Electronic Communications of the EASST, 2010)
Using the openETCS initiative as a starting point, we describe how open software can be applied in combination with platform-specific, potentially closed source extensions, in the development, verification, validation and certification of safety-critical railway control systems. We analyse the safety and security threats presented by this approach and discuss conventional operating system partitioning mechanisms, as well as virtualisation methods with respect to their potential to overcome these problems. Furthermore, we advocate a shift from open source to open models, in order to increase the development efficiency of combined open and proprietary solutions.